Some aspects of biology of Alepes djedaba (Forsskal) from Vera val, Gujarat - Raje, S G (Indian Journal of Fisheries, 2011)
Random samples of A. djedaba were collectedfrom the commercial landings of trawland gill nets operated by mechanized boats atVeraval. Total length (mm), weight (g), sexratio, maturity stage of females and gut contentswere recorded from fresh samples. Thematurity stages were classified according toI.C.E.S. system. For estimating the fecundity,5% formalin-preserved ovaries in stage Vwere used. The food of the species wasanalysed by volumetric and occurrencemethods. The index of preponderance wascalculated by the method of Natarajan andJhingran (1961).